Factors affecting the decision to use modern family planning methods among the indigenous people in Guimaras province - Galve, Cheena May S.
Increasing access to reproductive health services is necessary to improve maternal health and to reduce maternal mortality rates. As the indigenous peoples remain at disadvantaged in terms of the provision of health care services including sexual and reproductive health services, this study was conducted to determine the factors affecting the decision to use modern family planning (MFP) methods among the indigenous people (IP) in Guimaras. The study was conducted in the four municipalities of Guimaras Province, where six IP, locally known as ?Ati?, communities are located: Buenavista, Jordan, Sibunag, and Nueva Valencia. A total of 97 women IP who were users and non-users of family planning were interviewed. They belonged to the criteria set: in their reproductive age of 15 to 49 years old, has a partner, with at least one child, or pregnant during the period of data collection. Out of the 97 women, 36 (37%) were currently using MFP methods while 61 (63%) were non-users. Among the MFP methods, pills and injection were commonly used by the study participants. Current users of pill and injection obtained the MFP method and services from the barangay health station, barangay supply point officer, and the pharmacy. Using binary logistic regression, nine factors were found to significantly affect the decision of the study participants to use MFP method. These were the current age of the study participant, current age squared, being married, household income, household income squared, belief that family planning using modern methods is against Filipino culture, resident of San Nicolas in Buenavista, resident of San Miguel in Jordan, and membership in the Pantawid Pamilyang Pilipino Program (4Ps).